Emotional Detachment and Cyberbulling Among Generation Z in Samarinda City - Ziya Ibrizah; Reksa Burhan; Ahmad Ridha Mubarak; Ahmad Hidayah; Rosyid Nurrohman; Muhammad Nurdin Sanjaya; Rifaldy Sefruyanti Palungan (SEIKAT: Jurnal Ilmu Sosial, Politik dan Hukum, 2026)
This study examines emotional detachment and cyberbullying among Generation Z students in Samarinda and their dynamics in digital interactions. It uses a sequential explanatory mixed-methods design, beginning with a quantitative phase (questionnaires) followed by a qualitative phase (in-depth interviews). The quantitative sample included 150 students from three schools, with data collected using a 1–5 Likert scale and analyzed descriptively. The qualitative phase involved 30 informants and thematic analysis. Results show emotional detachment at a high level (mean 3.55) and cyberbullying at a moderate level (mean 2.99). Qualitative findings reveal that emotional detachment does not directly increase cyberbullying but creates a gap between empathy and action. Students generally recognize the harm of cyberbullying but tend to remain passive, avoid conflict, or not intervene. The study concludes that cyberbullying is influenced not only by individual behavior but also by emotional distance, digital communication patterns, low social courage, and limited collective response. It recommends strengthening empathy-based digital literacy, self-disclosure, social courage, and a healthy communication culture in schools.